2009
DOI: 10.1167/iovs.08-2781
|View full text |Cite
|
Sign up to set email alerts
|

An International Collaborative Family-Based Whole-Genome Linkage Scan for High-Grade Myopia

Abstract: Purpose Several nonsyndromic high-grade myopia loci have been mapped primarily by microsatellite markers and a limited number of pedigrees. In this study, whole-genome linkage scans were performed for high-grade myopia, using single nucleotide polymorphisms (SNPs) in 254 families from five independent sites. Methods Genomic DNA samples from 1411 subjects were genotyped (Linkage Panel IVb; Illumina, San Diego, CA). Linkage analyses were performed on 1201 samples from 10 Asian, 12 African-American, and 221 Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…In addition, 3 genetic markers ( DRD4 _VNTR, MAOA _VNTR, and COMT rs4680) were ascertained by the standard PCR procedures [22][23][24] . The GenCall scores of the loci in the current study ranged from 0.45 to 0.95; this is above the conventional cutoff point of 0.25 for inclusion [25] . The GenCall score (ranging from 0 to 1, the higher the better) is a quality measure for each genotype in the Illumina system that indicates how close a genotype is to the center of the cluster of other samples assigned to the same genotypes [26] .…”
Section: Genotyping Techniquesmentioning
confidence: 55%
“…In addition, 3 genetic markers ( DRD4 _VNTR, MAOA _VNTR, and COMT rs4680) were ascertained by the standard PCR procedures [22][23][24] . The GenCall scores of the loci in the current study ranged from 0.45 to 0.95; this is above the conventional cutoff point of 0.25 for inclusion [25] . The GenCall score (ranging from 0 to 1, the higher the better) is a quality measure for each genotype in the Illumina system that indicates how close a genotype is to the center of the cluster of other samples assigned to the same genotypes [26] .…”
Section: Genotyping Techniquesmentioning
confidence: 55%
“…27 This locus was further supported by an additional genome-wide linkage scan of Asian families. 37 Recently, a GWAS study on Singapore Chinese revealed that genetic variations in the noncoding region of CTNND2, the SNPs rs6885224 and rs12716080, were associated with high myopia. 33 The CTNND2 gene is located inside the linkage interval of MYP16.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear from this data whether this locus is distinct from MYP13. The results of the first large-scale study of high-grade myopia (254 families from 5 independent sites, 1411 subjects) tentatively confirmed the Xq28 locus although the peak LOD score was only 1.6.9, and these results appeared to only be confined to the Duke subset (Duke University Medical Center, Durham, NC, USA) using the DOM model (40). A much higher although non-significant LOD score of 2.4.0 was obtained for the MYP13 locus (Xq24), which again suggests confirmation, but was confined to the Cardiff (Wales) subset.…”
Section: X-linked Locimentioning
confidence: 91%
“…Li et al also identified a 9.9.7 cM region in the MYP3 locus (12q21) using the SNP approach rather than microsatellite analysis (40). Total HLOD scores for this region were 3.4.8 with strongest contributions from the Duke subset.…”
Section: Myp 2 Andmentioning
confidence: 99%